(untitled) (Acta Scientiarum. Biological Sciences, 2008)
The distribution and abundance of exotic and native species in levee neo-ecosystems were analyzed. No invasive species were found in unit A; their absence could be explained by the fluvial action of the Paraná river, extraordinary flood episodes and anthropic disturbances. Invasive species associated with the tidal regimen of the de la Plata river were present in units B and C, particularly Chinese privet (L. sinense), green ash (F. pennsylvanica), honey locust (G. triacanthos), Japanese honeysuckle (L. Japonica), blackberry ( Rubus spp.), box elder (A. Negundo ) and glossy privet (L. Lucidum).Native species showed low recovery values, both at a regional level and within each unit, with the exception of A. The neo-ecosystems with the greater degree of abandonment of units B and C exhibited dominance of exotic tree species and, to a lesser extent, recovery of native species of the original gallery forest (seibo, Erythrina crista galli; laurel, Nectandra falcifolia; canelón, Rapanea spp. and arrayán, Blepharocalyx tweediei).